2004
DOI: 10.1542/peds.113.6.1603
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Clinical Trial of a Home Safety Intervention Based in an Emergency Department Setting

Abstract: This educational and device disbursement intervention was effective in improving the home safety practices of caregivers of young children. Moreover, the ED was used effectively to disseminate home injury prevention information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
114
0
10

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 24 publications
1
114
0
10
Order By: Relevance
“…3 Particularly important is the potential opportunity for the ''teachable moment,'' where ED providers are exposed to high-risk patients who, in turn, may be more receptive to disease or injury-specific information. 10 The teachable moment may be most useful at the first medical intervention for the injury and less effective with repeated injuries of a similar nature. 24 The mean and median times from triage to discharge for patients in our chart review were 180 and 144 minutes, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Particularly important is the potential opportunity for the ''teachable moment,'' where ED providers are exposed to high-risk patients who, in turn, may be more receptive to disease or injury-specific information. 10 The teachable moment may be most useful at the first medical intervention for the injury and less effective with repeated injuries of a similar nature. 24 The mean and median times from triage to discharge for patients in our chart review were 180 and 144 minutes, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Given that approximately one-third of ED visit duration involves direct patient care, 25,26 there is a significant amount of time available for interventions when patients are waiting in triage or examination rooms. Educational interventions are most beneficial when also providing safety devices, as demonstrated in randomized trials where providing home safety devices 10 and booster seats 12 were significantly more effective in knowledge and behavior change compared to education-only interventions. It should be emphasized that the educational component is critical, and there is no evidence to show that just providing devices changes behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brief counseling in the EDs on behaviors and practices related to injury prevention leads to improved home safety, seatbelt, and bicycle helmet use. 56,57 School-and community-based programs that yield improvement in safety practices by parent safety education, home inspection, and the distribution of safety supplies seem to improve knowledge and behavior related to injury prevention and decrease the risk for injury. [58][59][60] Our study, although population based and the largest to date in the United States, has several important limitations.…”
Section: E548 Femur Fractures Associated Injuries Sociodemographic mentioning
confidence: 99%
“…18,20,21 While limited data supports the use of health educators in the pediatric ED, this research is novel because there is a paucity of information regarding 1) adolescents as the intervention recipients and 2) interventions focused on pregnancy and STI detection and prevention. 12,24,25 Several areas were identified that should inform future education efforts. First, while many HCPs advocated for protecting adolescent health and safety, their success may be impaired by knowledge deficits surrounding confidentiality and age of consent for sexual intercourse and medically emancipated conditions.…”
Section: Discussionmentioning
confidence: 99%